On freedom - Snyder, Timothy (New York : Crown, 2024)
"A brilliant exploration of freedom--what it is, how it's been misunderstood, and why it's our only chance for survival--by the acclaimed Yale historian and author of the #1 New York Times bestseller On Tyranny"--
Preface -- Introduction: Freedom -- Sovereignty -- Unpredictability -- Mobility -- Factuality -- Solidarity -- Conclusion: Government
Includes bibliographical references (pages 287-338) and index
Keywords: Liberty; Democracy -- United States; Political culture -- United States; Liberté.; freedom; Informational works; Documents d'information.